SIKAP MAHASISWA BAHASA INGGRIS TERHADAP PENGGUNAAN TEKNIK TEAM GAME TOURNAMENT (TGT) PADA MATA KULIAH READING COMPREHENSION III - HENDRA EKA PUTRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
This research was inspired because of the researcher previous research. Based on the result of the research, he found that there was a contradiction between the students’ enthusiastic and their score after appying Team Game Tournament (TGT) technique. They had highly positive to the use of the technique, but they had low score after doing the reading test. It was the reason why the researcher tried to reresearch about the trueness whether the technique was still possible to be used at Reading Comprehension classroom or not. This research was descriptive quantitative one. Respondent of the research was the third semester students of English department of Tarbiyah Faculty of STAIN Batusangkar registered in 2013/2014 academic year. Data of the research was collected by giving questionnaire and observation note. After analyzing the data of the research, it was known that the students’ attitude toward the use of Team Game Tournament (TGT)technique at Reading Comprehension III classroom was positive in which there were 16 students (42,1%) had positif attitude toward the use of the technkique.Kata kunci: Sikap Mahasiswa, Team Game Tournament